Narrativist Criticism of Historiography and the Interface Between Historiography and (Natural Science) and Between a Historical Construction and Literary Fiction - Horský, Jan (Dějiny – teorie – kritika, 2013)
With the contribution of Jan Horský and Jakub Češka, the editors of the journal Dějiny – teorie – kritika open a discussion of the issue of narrativism and narrativist criticism of historiography. In doing so, we would like to provoke a debate that would lead to a deeper reflection about the forms of historical narration with emphasis on interdisciplinary approach on the border between history and literary science.